ANALISIS KANDUNGAN LOGAM PADA LIPSTIK YANG BEREDAR DI KOTA BATUSANGKAR - Khaira, Kuntum (Program Studi Pendidikan Kimia, FKIP, Universitas Pattimura (Chemistry Education Study Program, Faculty of Teacher Training and Educational Sciences, Pattimura University), 2023)
Research has been conducted to analyze the content of heavy metals (Pb, Cd, Mn) in lipstick circulating in Batusangkar Market. Samples are lipsticks that are registered and not registered with BPOM with various brands, colors and prices sold in the batusangkar market and totaling 10 samples. The sample was destroyed using a mixture of nitric acid and hydrogen peroxide. Furthermore, the content of Pb, Cd and Mn was measured using Atomic Absorption Spectrophotometry (AAS). Based on the results of the analysis, the Pb content in the sample ranged from -6.875 mg/kg to 2.0305 mg/kg, Cd content 0.18 mg/kg to 0.52 mg/kmg/kg, Mn content -4.60 mg/kg up to 149.59 mg/kg. Lead was found in 4 out of 10 lipstick samples, heavy metal Cd was found in all lipstick samples and manganese was found in 8 out of 10 lipstick samples. Based on these results, it can be concluded that the heavy metal content in the electrical sample is below the specified limit so that it meets the requirements of the Regulation of the Head of the POM No. 17 of 2014 concerning requirements for microbial and heavy metal contamination in cosmetics.